THE DA'WAH RHETORIC OF USTADZ HANDY BONNY IN DELIVERING RELIGIOUS MESSAGES ON THE YOUTUBE CHANNEL @oneummahmovement - Amelia Lestari Br. Butar-butar; Muktarruddin Muktarruddin (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Digital platforms have reshaped how Islamic preachers, or da'i, communicate with younger audiences, and YouTube has become a central stage for this transformation. This study examines the da'wah rhetoric of Ustadz Handy Bonny on the YouTube channel @oneummahmovement, focusing on two episodes, KOUM #40 and KOUM #11, both addressing the theme of hijrah among young people. Following the qualitative case study tradition of Creswell and Poth (2024), narrative excerpts, viewer comments, and video documentation were examined descriptively. Findings show that Handy Bonny integrates the three Aristotelian pillars of ethos, pathos, and logos through colloquial diction, humor, and personal storytelling within a structured narrative moving from an opening anecdote to Qur'anic grounding and closing reflection. Audience comments reveal predominantly positive cognitive, affective, and conative responses, consistent with the uses and gratifications framework of Katz et al. (1973). The study concludes that this informal, emotionally resonant style effectively strengthens youth religious engagement in digital da'wah spaces.